Overview of contract farming in Thailand: Lessons learned - Songsak Sriboonchitta; Aree Wiboonpoongse (Asian Development Bank Institute (ADBI), 2008)
Contract farming is a means to assist small growers in gaining market access and reducing price risk, and as such it has attracted attention from development agencies and governments in developing countries. This paper reviews literature related to contract farming in Thailand and adds updated information based on field visits in 2007. Special attention is given to roles played by government in the initial stage of contract farming development. Conclusively, it is important for the public sector to create a favorable environment and infrastructure to encourage investment in agribusiness and to coordinate the concerned parties to raise agricultural productivity. The paper also evaluates the effectiveness of contract farming as a means to stabilize farmers' income and strategize agricultural development. The findings show that while the poorest farmers were not excluded from contract farming, special measures may be needed to encourage their full participation. In the long run, small farmers were able to accumulate production and management skills, thus improving their bargaining position. Together with improved infrastructure and a more competitive market due to farmers' innovation, the farmers' best choice may include non-contract production.
Keywords: Q13; Q17; L14; 330